Sharing is Caring sebagai Upaya Peningkatan Kualitas Hidup Pasien Gangguan Jiwa di RSKD Dadi Makassar - Budiman, Mutmainnah (Devotion : Jurnal Pengabdian Psikologi, 2023)
The lack of life support for patients with mental disorders is currently of great concern. Various parties are working together to help patients with mental disorders, both from the family and the hospital. However, what is found in reality is just a mere talk. However, it is important to realize that they simply need to be acknowledge, supported, and recognized like humans in general. This can be done by actively listening to stories or complaints from of ODGJ (Orang dengan gangguan Jiwa / people with mental disorder) patients to their improved quality of life. Sharing is caring is one of the activities aimed at providing life support to ODGJ patients. This activity is carried out by providing time for patients to share their stories, experiences, and complaints while in the Dadi Makassar hospital ward. The results of therapy indicate that this activity is effective for ODGJ patients in fostering the spirit of recovery and improving their quality of life.